خصائص مصادر المعلومات التربوية للبحوث المنشورة في مجلة كلية المعلمين / الجامعة المستنصرية : دراسة تحليلية للمدة من 1994 - 2000 - جواد، سهلة علوان; عبدالله، خالدة عبد (الجامعة المستنصرية - كلية التربية, 2009)
تضمن البحث دراسة خصائص مصادر النتاج الفكري التربوي المعتمد في بحوث مجلة كلية المعلمين ( ) في الأعداد (1 - 25) للسنوات 1994-2000، وذلك من خلال تحليل الإشارات البيليوغرافية المستشهد بها في تلك البحوث للتعرف على نوعية المصادر وخصائصها الموضوعية والشكلية والزمنية باستخدام أسلوب التحليل الإحصائي، مع إجراء المقارنات اللازمة التي ظهرت خلال البحث من خصائص الموضوعات التي اشتملت عليها بحوث المجلة. توصلت الدراسة إلى عدد من النتائج منها: أن موضوعات الأدب واللغة العربية مثلت النسبة الأكبر لعدد الإشارات، وان الكتب هي أكثر الأشكال المصادر إشارة لم يتفق الباحثة على موقع محدد لتثبيت البيانات الببليغرافية مع نص واضح في حقول البيانات الببليغرافية المدونة، وخصلت الدراسة إلى عدد من التوصيات منها: اشتراك المكتبات الجامعية بالمجلات العلمية، وتمكن الباحثين من الاطلاع على مصادر المعلومات الحديثة كبحوث الدوريات العلمية والرسائل الجامعية بإعداد المستخلصات والكشافات التحليلية وجعلها متاحة للباحثين والتأكيد على توثيق مصادر المعلومات ضمن شروط النشر في المجلات العلمية بإتباع أساليب موحدة في إعداد قائمة المصادر واكتمال حقول البيانات الببليوغرافية وفقا لصيغ موحدة. The research includes studying the characteristics of educational and intellectual literature endorsed by the articles of Teachers College Periodical (Majalt Kulait Al-Mualimeen) issue no. ١-٢٥(١٩٩٤-٢٠٠٠) through analyzing bibliographical citation used in these articles to be familiar with the quality sources and their annual, formal and objective characteristics by using statistical analysis through conducting required comparisons which emerge from the conclusion within the articles published in this periodical .The study has revealed of results: first, topics of the Arabic art and language and the largest part of citations number. \ Second , books use these citations mostly .Third, researchers do not use a specific place for writing down the bibliographic data, besides, there is obvious shortcoming in the fields of these written data. The study has made number of recommendations: participation of the universities library in the scientific periodicals. Enabling the research hers to study the sources of the recent information like researchers of the scientific periodicals, theses and dissertations of the universities by preparing abstracts and analytic indexes and making them available for researchers. \ Documentation of the information should be made according to the publishing conditions of the scientific periodicals by following integrated styles in preparing the sources list. Finally, completing the fields of bibliographic data according to an integrated style.
Keywords: العراق -- مصادر المعلومات التربوية -- البحوث العلمية -- الاشارات البيبلوغرافية -- الدوريات العلمية -- الإنتاج الفكري